How the withdrawal of global correspondent banks hurts Emerging Europe - Lea Borchert; Ralph de Haas; Karolin Kirschenmann; Alison Schultz (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Correspondent banks allow local banks in emerging markets to access the international payments system. This helps local banks to make cross-border payments, clear currencies, and provide trade finance. The recent retrenchment of global correspondent banks following the increased costs of financial crime compliance may therefore disrupt international trade. This policy brief shows that the withdrawal of correspondent banks from Emerging Europe has negatively and substantially affected the exports of this region. Exploiting an unexpected change in the U.S. regulator's enforcement of financial crime legislation we compare industry-level bilateral trade flows of countries experiencing a high withdrawal with those that maintain their correspondent bank relationships. We find that the decreased availability of international payment and trade finance services has considerable negative effects on exports. This negative effect is stronger for trading partners that are geographically more distant. A survey of 93 local banks confirms that banks face growing difficulties in performing cross-border payments and in clearing currencies. In particular, access to the U.S. financial system is severely inhibited and local banks can only imperfectly substitute lost correspondent bank relationships with new partners from Russia and Austria.
Keywords: 330